FORTIFICATION OF DRY SKIN SHRIMP (Mysis relicta) PROTEIN CONCENTRATE IN THE PROCESSING OF ATOM CRACKERS TOWARDS CONSUMER ACCEPTANCE - Rianti, Ernita; Suparmi, Suparmi; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was aimed to determine the effect of fortification of dry skin shrimp (Mysis relicta) protein concentrate on atom crackers processing. The method used was an experimental method using a factorial Completely Randomized Design (CRD), with 4 levels of treatment of namely without adding dry skin shrimp protein concentrate (K0), 5% of dry skin protein concentrate (K1), 10% of dry skin protein concentrate (K2), and 15% of dry skin protein concentrate (K3). The parameters measured in this study were organoleptic test, moisture, protein, fat, ash content and flower power. The results showed that the addition 10% of dry skin shrimp protein concentrate (K2) in the processing of atom crackers was most preferable by consumer acceptance with an average value of like (35 panelists) and like extremely (41 panelists) which was 43.75% and 51.52%, respectively. The characteristics of atom crackers were brownish appearance (3.59), distinctive aroma of dry skin shrimp protein concentrate (3.45), savory flavor of dry skin shrimp protein concentrate (3.43), and crispy texture (3.53). Meanwhile for chemical values of moisture, protein, fat, ash content and flower power were 3.14%, 13.96%, 3.82%, 1.38%, and 125.18% respectively. Keywords: Atom crackers.Concentrate.Rebon shrimp